The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/08933189211029561
|View full text |Cite
|
Sign up to set email alerts
|

“They Are Nothing More Than His Spies on the Floor”: Local Employees’ Sensemaking and Interpretation of Expatriates’ Roles and Responsibilities

Abstract: This study examines how local employees gain information and make sense of new expatriates’ roles and responsibilities in multinational corporations by applying Weick’s sensemaking theory. Data were collected through semi-structured interviews of 17 local employees working for a Japan-based automotive manufacturing company in a Midwestern U.S. city. Results revealed that local employees extracted cues from their environment to make sense of expatriates’ roles and responsibilities by communicating directly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…However, an organization and its members with primarily local/limited audiences tend to focus their identity communication efforts to more immediate others, such as a community, family, and friends.” (Askay & Gossett, 2015, p. 621).3. Explanations; for example, while the sentence “As employees move to and work in another country, their relationships with local employees (i.e., host country nationals; HCNs) play an important part in their expatriate success” (Wyant & Kramer, 2022, p. 125) does not define “local” per se, it provides information about what the author means by “local employee.”…”
Section: How To Do a Reflexive Reviewmentioning
confidence: 99%
“…However, an organization and its members with primarily local/limited audiences tend to focus their identity communication efforts to more immediate others, such as a community, family, and friends.” (Askay & Gossett, 2015, p. 621).3. Explanations; for example, while the sentence “As employees move to and work in another country, their relationships with local employees (i.e., host country nationals; HCNs) play an important part in their expatriate success” (Wyant & Kramer, 2022, p. 125) does not define “local” per se, it provides information about what the author means by “local employee.”…”
Section: How To Do a Reflexive Reviewmentioning
confidence: 99%
“…Research normally considers such violation in expectation as detrimental to the relationship between expatriates and HCNs. For example, Wyant and Kramer (2021) found that HCNs tended to interpret expatriates' roles and responsibilities negatively when they found a mismatch between their expectations for expatriates and their experiences. However, we propose that not all these incongruence situations are equally detrimental to the expatriates and HCNs dyadic relationship.…”
Section: Model Of the Acculturation Processmentioning
confidence: 99%
“…This is not documented in the workplace. However, it is thought that local managers who observe the state of the workplace will understand the working styles of expatriates and their expected working styles and adjust their awareness and behavior (Wyant and Kramer, 2021). This is because it is necessary to work in a way that meets the expectations of the workplace to be evaluated.…”
Section: Literature Reviewmentioning
confidence: 99%